BALANCED SCORECARD BASED PERFORMANCE MEASUREMENT & STRATEGIC MANAGEMENT SYSTEM - Paulina Permatasari (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Developing strategy and performance measurement are an integral part of management control system. Making strategic decision about planning and controlling require information regarding how different subunits in organization work. To be effective, performance measurement, both financial and non-financial must motivate manager and employees at different levels to force goal accomplishment and organization strategic. An organization's measurement system strongly affects the behavior of people both inside and outside the organization. If companies, are to survive and prosper in information age competition, they must use measurement and management systems derived from their strategies and capabilities. Unfortunately, many organizations espouse strategies about customer relationships, core competencies, and organizational capabilities while motivating and measuring performance only with financial measures. The Balance Scorecard retains financial measurement as a critical summary of managerial and business performance, but it highlights a more general and integrated set of measurements that link current customer, internal process, employee and system performance to long term financial success.